Glucocorticoids and histone deacetylase inhibitors cooperate to block the invasiveness of basal-like breast cancer cells through novel mechanisms - Law, ME (2012)
Aggressive cancers often express E-cadherin in cytoplasmic vesicles rather than on the plasma membrane and this may contribute to the invasive phenotype of these tumors. Therapeutic strategies are not currently available that restore the anti-invasive function of E-cadherin in cancers. MDA-MB-231 cells are a frequently used model of invasive triple-negative breast cancer, and these cells express low levels of E-cadherin that is mislocalized to cytoplasmic vesicles. MDA-MB-231 cell lines stably expressing wild-type E-cadherin or E-cadherin fused to glutathione S-transferase or green fluorescent protein were used as experimental systems to probe the mechanisms responsible for cytoplasmic E-cadherin localization in invasive cancers. Although E-cadherin expression partly reduced cell invasion in vitro, E-cadherin was largely localized to the cytoplasm and did not block the invasiveness of the corresponding orthotopic xenograft tumors. Further studies indicated that the glucocorticoid dexamethasone and the highly potent class I histone deacetylase (HDAC) inhibitor largazole cooperated to induce E-cadherin localization to the plasma membrane in triple-negative breast cancers, and to suppress cellular invasion in vitro. Dexamethasone blocked the production of the cleaved form of the CDCP1 (that is, CUB domain-containing protein 1) protein (cCDCP1) previously implicated in the pro-invasive activities of CDCP1 by upregulating the serine protease inhibitor plasminogen activator inhibitor-1. E-cadherin preferentially associated with cCDCP1 compared with the full-length form. In contrast, largazole did not influence CDCP1 cleavage, but increased the association of E-cadherin with γ-catenin. This effect on E-cadherin/γ-catenin complexes was shared with the nonisoform selective HDAC inhibitors trichostatin A (TSA) and vorinostat (suberoylanilide hydroxamic acid, SAHA), although largazole upregulated endogenous E-cadherin levels more strongly than TSA. These results demonstrate that glucocorticoids and HDAC inhibitors, both of which are currently in clinical use, cooperate to suppress the invasiveness of breast cancer cells through novel, complementary mechanisms that converge on E-cadherin.